ZrxCa30-xP70 thermoluminescent bio glass, structure and elasticity. (July 2021) - Kumar, G. Anil; Rambabu, Y.; Guntu, Ravi Kumar; Sivaram, K.; Reddy, M. Sreenath; Rao, Ch. Srinivasa; Venkatramu, V.; Kumar, V. Ravi; Sriman Narayana Iyengar, N. Ch.
Abstract: Phosphate glasses of calcium oxide have been well proved materials for various bio bones and dental implants. However, still there is a lot of scope and demand to produce efficient elastic bio implants and resource. In view of this, Zrx Ca30-x P70 phosphate materials are prepared by using melt quenching method. Bio, physical, thermoluminescence and elastic techniques are used to characterize the samples. Additionally, simulated body fluid was prepared and it is used especially for bio techniques. Further, the glasses are taken for different dose (~0, 10, 20 & 50 kGy) of gamma irradiation around half an hour. And again similar techniques are used to characterize the samples. All the findings from bio, physical, thermoluminescence and elastic characterization results are analysed and took for better comparison with previous studies to develop various bio bone (or) bio dental resource. Structural reports suggests that the Zrx Ca30-x P70 materials were glassy before immersion in SBF solution and immersed (~720 h) samples are showing partial ceramic nature. The weight loss and pH reports suggests them for alternative bio resource as a bio bones and dental implants. Observed thermal stability, microhardness and elastic modulus evaluations of Zrx Ca30-x P70 materials in required standards are also additional advantage. Furthermore, thermoluminiscence (TL) under different γ-irradiation doses is reported for glasses with and without immersing in a simulated body fluid. The glasses lose TL intensity when immersed in simulated body fluid for nearly 720 h. This is useful to modulate bio-behaviour in terms of hydroxyapatite layer growth on the glass surface. Graphical abstract: Image 1